International strategy for SMEs: criteria for foreign markets and entry modes selection. Issue 2 (13th May 2014) - Musso, Fabio; Francioni, Barbara
Abstract : Purpose: – The purpose of this paper is to examine the internationalization of small- and medium-sized enterprises (SMEs) in regard to the international market selection (IMS) and entry mode selection (EMS) processes. Design/methodology/approach: – To achieve this, an examination of the degree of systematic/active behaviour during IMS and EMS on a sample of 221 SMEs was conducted. Moreover, the paper sought to comprehend whether SMEs select foreign market and entry mode in a separate and sequential way, and whether there is a relationship between the sequentiality of IMS and EMS, on one side, and SME behaviour during these two processes, on the other side. Findings: – Results revealed that SMEs have a non-systematic and passive behaviour during IMS and EMS, respectively. Moreover, a high predilection in performing the two processes contemporaneously or without any logic was found. Finally, a strong relation between sequentiality of IMS and EMS and degree of systematic and active behaviour during the processes existed. Originality/value: – In this study, using a sample of SMEs located in a region of Italy, SME behaviour in the IMS and entry mode choice processes was tested.